Strength Characteristics of Microbial Induced Calcite Precipitate/Cement Stabilized Laterite Blocks - Abdullahi, S.; Amartey, B. H. S.; Kaura, J. M.; Amartey, Y. D. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2024)
This paper assesses the strength characteristics of microbial induced calcite precipitate/cement stabilized laterite blocks. To achieve this, the compressive strength of unmodified lateritic soil blocks, Bacillus coagulans calcite precipitate modified lateritic soil blocks, cement modified lateritic soil blocks as well as the combined effects of the Bacillus coagulans calcite precipitate and 5% cement stabilized lateritic soil blocks were determined. Bacillus coagulans bacteria was used as the bio calcination agent and ordinary Portland cement as the stabilizer. The B. coagulans was mixed at various concentrations using the McFarland standard and cement was replaced at 5% to 20% replacement levels after which the crushing strengths were determined considering various curing ages. The compressive strength increased at the various curing ages ranging from 0.9 N/mm2 to 2.0 N/mm2 at 7 days, 1.3 N/mm2 to 2.1 N/mm2 at 14 days, 1.5 N/mm2 to 2.15 N/mm2 at 21 days and 1.65 N/mm2 to 2.5 N/mm2 at 28 days for all the stabilized blocks with varying concentrations of B. coagulans suspension. The compressive strength of the cement stabilized laterite blocks increased with an increase in percentage of cement replacement, and also with increasing B. coagulans suspension density for stabilized microbial induced calcite precipitate (MICP) laterite blocks. The 5% cement stabilized MICP laterite blocks performed better than cement stabilized laterite blocks with 20% cement replacement. The optimum concentration was achieved at Bacillus coagulans suspension of 2.4 x 109 cell/ml and 5% cement replacement at 28 days curing age with compressive strength value of 4.2 N/mm2. Based on the study conducted, it is recommended that for production of laterite blocks, a quantity of 5% cement replacement for stabilization of laterite may be used in addition to Bacillus coagulans to produce stronger laterite blocks